Product comparison between local product and technology aided Mambong pottery - K. Ahmad; J. J. Mohamed (Universiti Malaysia Kelantan, 2016)
There are various traditional Malay potteries such as Labu Sayong, Buyung and Terenang. Kelantan traditional pottery known as Mambong. The objectives of this research are to compare and characterize the density, strength, physical appearance and shrinkage of traditional and slip casted Mambong pottery. Traditional Mambong pottery has been brought from the potter at Mambnog village and slip casted Mambong pottery is made by using slip casting method. Density of sample is measured by using Archimedes principal. Traditional Mambong pottery show the higher value of density compared to slip casting Mambong pottery. The average value of density for traditional Mambong pottery was 1.763 g/cm3 , while the average value of density for Mambong pottery that was fabricated via slip casting was 1.461 g/cm3 . Due to the presence of iron in clay, the colour of Mambong pottery changes from brown to reddish-brown after firing process. Traditional Mambong pottery shows the higher percentage of dry shrinkage which was 9.76 % compared to slip casting Mambong pottery which was 5.72 %. Traditional Mambong pottery also shows the higher percentage of fired shrinkage which was 1 % compared to slip casting Mambong pottery which was 0.58 %. In conclusion, by using slip casting technique, density, physical appearance and shrinkage of pottery can be improved.